THE EFFECT OF GOOD CORPORATE GOVERNANCE, SALES GROWTH, AND CAPITAL INTENSITY ON TAX AVOIDANCE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) IN 2019-2021 - Tutupoho, Mutmaina; Abdul Hadi Sirat; Fadli Ali Taslim (UIN Raden Mas Said Surakarta, 2023)
This study aims to assist investors in providing an overview of the factors that can influence tax evasion by analyzing the Influence of Good Corporate Governance, Sales Growth and Capital Intensity on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for 2019-2021. Good Corporate Governance, Sales Growth and Capital Intensity are used as independent variables and Tax Avoidance as the dependent variable. This study used a purposive sampling technique with a sample of 88 manufacturing companies that met the research criteria for the 2019-2021 period from a population of 193 companies. This study used Multiple Linear Regression Analysis to test the hypothesis. The results of this study indicate that partially Good Corporate Governance, Sales Growth and Capital Intensity significantly influence Tax Avoidance, and simultaneous hypothesis testing shows that Good Corporate Governance, Sales Growth and Capital Intensity significantly influence Tax Avoidance together.